Deregulation of seven CpG island-harboring miRNAs in bladder cancer: miR-155 and miR-23b as the most promising oncomiRs - Pençe, S; í–zbek, E; Ozan Tiryakioğlu, N; Ersoy Tunali, N (Cellular and Molecular Biology, 2016)
Analyses of differential miRNA expressions in tumor and normal tissues can identify specific miRNAs involved in cancer pathogenesis, which can then be used as diagnostic, therapeutic and prognostic biomarkers. In this respect, we aimed to investigate expression levels of seven CpG island-harboring miRNAs in 50 paired UBC tissues by qRT-PCR. miR-21 and miR-155 were found to be significantly upregulated, and miR-23b, miR-126, miR-129-5p, miR-143a and miR-218-5p were downregulated. ROC analysis indicated miR-155 as the most promising candidate for discrimination of tumors from healthy tissue, and miR-23b for the discrimination of early stage from late stage tumors.